The welfare effects of persuasion and taxation: Theory and evidence from the field - Matthias Rodemeier; Andreas Löschel (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2020)
How much information should governments reveal to consumers if consumption choices have uninternalized consequences to society? How does an alternative tax policy compare to information disclosure? We develop a price theoretic model of information design that allows empiricists to identify the welfare effects of any arbitrary information policy. Based on this model, we run a natural field experiment in cooperation with a large European appliance retailer and randomize information regarding the financial benefits of energy-efficient household lighting among more than 640,000 subjects. We find that full information disclosure strongly decreases demand for energy efficiency, while partial information disclosure increases demand. More information reduces social welfare because the increase in consumer surplus is outweighed by the rise in environmental externalities. By randomizing product prices, we identify the optimal tax vector as an alternative policy and show that sizable taxes on energy-inefficient products yield larger welfare gains than any information policy. We also document an important policy interaction: information provision dramatically reduces attention to pecuniary incentives and thereby limits the effectiveness of taxes.
Keywords: D61; D83; H21; Q41; Q48; 330; persuasion; optimal taxation; internality taxes; field experiments; energy efficiency; behavioral public economics